HUBUNGAN LINGKUNGAN KELAS TERHADAP KELAINAN REFRAKSI MIOPIA PADA SISWA KELAS 5 SD DI SD X SEMARANG - Lutfi Andrias; Hanifa Maher Denny; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Myopia is the most common human eye disorder in the world. for this refractive state, the retina is located behind the focal plane so that a concave lens is needed to move the focal plane back to the retinal plane, restoring a focused, clear image. definition of myopia vary, but generally an eye is considered myopic if a negative spherical equivalent correction of at least 0.5 diopters is needed to restore emmetropia, the refractive state in which image are focused on retina. because of varying definition, the reported prevalence of myopia varies. , The purpose of this study was to determine the relationship of the classroom environment to refractive error myopia in primary school students of class 5 in X in Semarang. This study uses a quantitative approach with cross sectional approach. Population and sample in this study were all students of class 5 in SD X Semarang total of 54 students. The independent variable in this study is visibility to the front of the class, local lighting, distance reading and writing, as well as the position of reading and writing. The dependent variable in this study is the refractive error myopia. Results of analysis by using chi - square showed that there is a relationship between visibility to the front of the refractive error myopia (p - value 0.05). Then there was no association of local illumination (p - value 0194), the distance to read and write (p - value 0.474), and the position of reading and writing (p - value 0.324) with refractive error myopia. This study also suggested schools to conduct routine screening and periodic on myopia and other health problems that could potentially occur on school students